18 Exploring the validity of VentriJect Seismofit® for estimating peak oxygen uptake in people with coronary heart disease. (21st November 2022) - Myers, Anna; Ali, Ali; Kudiersky, Nik; Søgaard, Peter; Schmidt, Samuel; Girard, Wilfrid; O'Doherty, Alasdair; Nichols, Simon
Abstract : Background: Peak oxygen uptake (&Vdot;O2 peak) predicts all-cause mortality and can indicate the effectiveness of exercise-based cardiovascular rehabilitation (CR) in people living with coronary heart disease (CHD). Maximal cardiopulmonary exercise testing (CPET), the gold standard method of measuring &Vdot;O2 peak, is expensive, time-consuming, and rarely used in CR. Furthermore, current methods to estimate &Vdot;O2 peak in CR lack accuracy. A promising new device, that uses a quick (5-minute) resting seismocardiography measurement within an algorithm to estimate &Vdot;O2 peak, is strongly associated with &Vdot;O2 peak in healthy people (r = .90). However, the validity of VentiJect Seismofit in CHD has not been investigated. Aim: To explore the validity of the existing Ventriject Seismofit algorithm for predicting &Vdot;O2 peak in people with CHD. Methods: Between August and November 2022, up to 24 participants aged ≥18 years, with a history of CHD and currently enrolled in community-based phase IV CR will be recruited. Participants will have their &Vdot;O2 peak estimated using the VentriJect Seismofit (twice 20 minutes apart to assess repeatability), complete a maximal CPET on a cycle ergometer followed by a brief questionnaire about their experience of participating in a maximal CPET, and the VentriJect Seismofit device measurement. Results: Results from this study will be used to assess the validity of the current VentriJect Seismofit algorithm, for estimating &Vdot;O2 peak in individuals with CHD. It will also assess the repeatability of the VentriJect Seismofit &Vdot;O2 peak estimate in this population. Qualitative feedback will provide insight into participants perceptions of participating in a maximal CPET and having &Vdot;O2 peak measurements taken by VentriJect Seismofit. Conclusion: Data from this exploratory validation study will support future grant application to conduct a definitive validation study in people with CHD. If the device is demonstrated to provide an accurate and reliable estimate of &Vdot;O2 peak in this population, it would represent a convenient and cost-effective method to be widely implemented in cardiac rehabilitation programmes.